Teaching Electronic Music: Cultural, Creative, and Analytical Perspectives, a cura di Blake Stevens; Giovanni Mori, Live Coding? What Does it Mean? An Ethnographical Survey on an Innovative Improvisational Approach - Leo Izzo (Musica Docta)
This miscellany, edited by Blake Stevens, brings together twelve papers on the teaching of electronic music in higher education. Stevens’ approach in organising and introducing the miscellany aims to overcome the traditional separation between musicology education and the teaching of composition. The essays in the collection provide a varied overview of the topic, ranging from methodological and organisational proposals for innovative didactics to in-depth studies of specific areas of electronic music and descriptions of the compositional practices of individual musicians. Giovanni Mori revisits a 2017 doctoral thesis on the phenomenon of live coding, a performance practice that has spread since the early 2000s in which musicians control the sonic outcome by modifying a software code in real time. Mori’s text is the first monograph on the subject and, as the title suggests, aims to define this way of making music from an ethnographic perspective. The author traces the cultural and historical origins of this musical movement and examines the operational specifics of live coding, which lies halfway between composition and improvisation. Through ethnographic research, including the use of digital communication platforms, he portrays a community rooted in the principles of knowledge sharing and participation.